Existence of Solutions for Boundary Value Problem of a Caputo Fractional Difference Equation - Zhiping Liu; Shugui Kang; Huiqin Chen; Jianmin Guo; Yaqiong Cui; Caixia Guo (Discrete Dynamics in Nature and Society)
We investigate the existence of solutions for a Caputo fractional difference equation boundary value problem. We use Schauder fixed point theorem to deduce the existence of solutions. The proofs are based upon the theory of discrete fractional calculus. We also provide some examples to illustrate our main results.